Effectively alleviate rheumatoid arthritis via maintaining redox balance, inducing macrophage repolarization and restoring homeostasis of fibroblast-like synoviocytes by metformin-derived carbon dots - Rui Zhang; Xingyu Lin; Rongjie Lin; Zhenbin Chen; Chenfang Miao; Yao Wang; Xiaoqin Deng; Jianlong Lin; Shishui Lin; Shaohuang Weng; Min Chen (Journal of Nanobiotechnology)
Abstract Overproduction of reactive oxygen species (ROS), elevated synovial inflammation, synovial hyperplasia and fibrosis are the main characteristic of microenvironment in rheumatoid arthritis (RA). Macrophages and fibroblast-like synoviocytes (FLSs) play crucial roles in the progression of RA. Hence, synergistic combination of ROS scavenging, macrophage polarization from pro-inflammatory M1 phenotype towards M2 anti-inflammatory phenotype, and restoring homeostasis of FLSs will provide a promising therapeutic strategy for RA. In this study, we successfully synthesized metformin-derived carbon dots (MCDs), and investigated the antirheumatic effect in vivo and in vitro. Designed MCDs could target inflamed cells and accumulate at the inflammatory joints of collagen-induced arthritis (CIA) rats. In vivo therapeutic investigation suggested that MCDs reduced synovial inflammation and hyperplasia, ultimately prevented cartilage destruction, bone erosion, and synovial fibrosis in CIA rats. In addition, MCDs eliminated the cellular ROS in M1 phenotype macrophages in RA microenvironment through the enzyme-like catalytic activity as well as inhibiting NOD-like receptor family, pyrin domain containing 3 (NLRP3) inflammasome signaling pathway, effectively polarizing them into the M2 phenotype to realize the anti-inflammatory effect. Furthermore, MCDs could inhibit the proliferation, migration, and fibrosis of inflamed FLSs. Mechanistically, MCDs restored the homeostasis of FLSs while reducing the level of synovial inflammation by blocking IL-6/gp130 signaling pathway. Combined with preferable biocompatibility, MCDs offer a prospective treatment approach for RA.